한국학입문 수업에서의 PBL 적용: 에듀테크 사례를 중심으로 - 류정민(Jamie Jungmin Yoo) (한국콘텐츠학회 논문지, 24(10), 2024)
본 논문은 학부 연계전공 필수 과목인 <한국학입문>의 설계에 “프로젝트 기반학습(Project-Based Learning, PBL)” 방법론을 적용한 사례를 분석하고 그 효과를 고찰하는 것을 목적으로 한다. 본 수업은 기존의 연대기적 강의식 수업에서 벗어나 학생들 스스로 학습 대상을 비판적으로 해석하고 프로젝트를 통해 해결 방안을 찾아가는 방식으로 재구성하였다. 특히 현 한국사회의 이슈 중 "교육"과 "테크놀로지"를 핵심어로 설정하고 구체적인 주제로 “에듀테크”의 효과와 가능성에 대해 논의하였다. 전체 15주의 과정은 주제별 8단계로 나누어 진행되었으며, 플립 러닝 (flipped learning)을 응용하여 학생들은 선행학습을 시행하고 수업 전 감상문을 제출하였으며, 수업은 토론과 교수자의 강의, 그리고 프로젝트를 위한 조별 활동 등으로 이루어졌다. 본 수업에서 시도한 PBL 교육은 학생들의 자기주도 학습능력, 비판적 사고력, 문제 해결능력, 그리고 사회참여 의식의 함양에 효과적인 방식임을 보여주었다. 한편, 대규모 수업에 적용 시 노정되는 문제점, 기술적 지원의 현실적 한계 등의 개선점 또한 확인되었다. 본 연구를 통해 PBL을 활용한 대학 교육의 혁신 가능성을 실험하여 이를 통해 향후 학습자 중심의 교육모델을 개발해 나갈 수 있도록 실증적 기반을 마련할 수 있도록 노력하였다. This study aims to analyze a case of applying the "Project-Based Learning (PBL)" methodology to the design of “Introduction to Korean Studies”, a required course for undergraduate interdisciplinary majors, and to examine its effects. The course was restructured to move away from the traditional chronological lecture-style teaching, allowing students to critically interpret the subject matter themselves and find solutions through projects. In particular, "education" and "technology" were set as key words among current issues in Korean society, and the effects and possibilities of "EduTech" were discussed as a specific topic. The entire 15-week course was divided into 8 stages by theme, and by applying flipped learning, students conducted prior learning and submitted reflection papers before class. The classes consisted of discussions, lectures by the instructor, and group activities for projects. The PBL education attempted in this course proved to be an effective method for cultivating students' self-directed learning ability, critical thinking skills, problem-solving skills, and awareness of social participation. On the other hand, issues that arise when applied to large-scale classes and practical limitations of technical support were also identified as areas for improvement. Through this study, we attempted to experiment with the possibility of innovation in university education using PBL, thereby striving to provide an empirical basis for developing learner-centered educational models in the future. KCI Citation Count: 0